Koszmar Nazona - Puk, Marlena (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2008)
In this article the author presents and briefy discusses a short story of Antonio Tabucchi entitled Sogno di Publio Ovidio Nasone, poeta e cortegiano, published in the collection of stories: Sogni di sogni. The novelist imagines Ovid transformed into a big butterfy coming back to Rome and describes the consequences of this metamorphosis.
Ovid’s nightmare
Keywords: Ovidius; Metamorphosis; Antonio Tabucchi; Dream